U. von Wilamowitz-Moellendorff (1848–1931) and G. Murray (1866–1957): Correspondence 1894–1930 Revisited - Kostyleva, Tatiana (Hyperboreus, 2016)
The prolonged correspondence of Ulrich von Wilamowitz-Moellendorff and Gilbert Murray was summarised by Murray himself late in his life (Antike und Abendland, 1954). Once Wilamowitz’ side of the correspondence – Murray’s letters are lost – was published by A. Bierl, W. M. Calder III and R. L. Fowler in 1991, it revealed the correspondents’ scholarly and personal relations to have been more complex. A selection of episodes pivotal to the correspondence is arranged in this article in the way witnessing not only the variety of the correspondents’ talents and undertakings, but also the differences inherent in their ways.